Forecasting the Growing Demand for Inpatient Beds Using Hospital Efficiency Indicators - Salma Aribatun Najihah; Andi Suhenda; Dini Mariani; Ari Sukawan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The quality of inpatient services in hospitals is strongly influenced by the efficiency of bed utilization, which is measured using key indicators such as Bed Occupancy Rate (BOR), Average Length of Stay (AvLOS), Turnover Interval (TOI), and Bed Turnover (BTO). Preliminary findings at Majalengka District Hospital showed that BOR remained below the optimal standard, AvLOS showed a gradual increase, TOI continued to decline, and BTO was excessively high. These patterns indicate the need to project inpatient bed requirements for the years 2025–2029. This study aimed to predict inpatient bed requirements based on inpatient service efficiency indicators. A descriptive quantitative study with a prospective approach was conducted. Secondary data on inpatient activities from 2022–2024 were collected using purposive sampling. Linear regression analysis was applied to predict inpatient days and patient discharges, while BOR and TOI calculations were used to estimate the number of beds required. The findings indicate that inpatient bed utilization at Majalengka District Hospital during 2022–2024 was still inefficient. Although the number of beds decreased, inpatient days and patient discharges continued to rise, reflecting increasing demand for inpatient services. Based on the standard BOR of 75–85% and TOI of 1–3 days, the projected bed requirement ranges from 167–292 beds in 2025 and increases to 212–368 beds by 2029. In conclusion, inpatient bed requirements at Majalengka District Hospital are expected to continue increasing, highlighting the need for regular evaluation and strategic planning of bed capacity.Keywords: prediction; bed requirement; efficiency; hospital